Social capital in Eastern Europe : Poland an exception? - Lasinska, Katarzyna (Springer Fachmedien Wiesbaden, 2013)
Katarzyna Lasinska deals with the consequences of democratic transitions in Middle and Eastern Europe. By selecting specific sets of countries according to the main explanations such as Catholic tradition, transformation process and communist legacies, the author identifies key factors explaining particular findings in Poland. Thank to systematically used comparative research strategy the pitfalls of idiosyncratic argumentation are successfully avoided. Through inclusion of religious tradition as an explanative factor the results go beyond the commonly used East-West comparisons. The author presents a comprehensive picture of complex conditions and different processes for social capital building across Eastern European societies.   Contents ·     Conceptualisation of social capital in a broad sense: trust, social networks and norms and values ·     Comparative study of Eastern European societies ·     Analysis of social capital building in post-communist societies ·     Quantitative analysis of the impact of religious tradition on social capital building ·     Factors explaining specific findings concerning low stock of social capital in Poland are identified     Target groups ·        Scholars and students in the political sciences, political sociology, sociology of religion, comparative politics ·        International and national NGOs, civil society players, Policy-makers, social networks activists, journalists and political analysts     Author Katarzyna Lasinska is a lecturer at the Chair for Political Science and International Comparative Social Research, University of Mannheim.